A cognitive definition of computational thinking in primary education. (April 2022) - Tsarava, Katerina; Moeller, Korbinian; Román-González, Marcos; Golle, Jessika; Leifheit, Luzia; Butz, Martin V.; Ninaus, Manuel
Abstract: There is increasing effort to integrate Computational Thinking (CT) curricula across all education levels. Therefore, research on CT assessment has lately progressed towards developing and validating reliable CT assessment tools, which are crucial for evaluating students' potential learning progress and thus the effectiveness of suggested curricular programs. Several CT assessment tools were developed for elementary, high-school, and university students over the last years. Moreover, associations between CT scores and other cognitive abilities were unraveled. However, studies on the topic in primary school level are scarce. Like the general concept of intelligence, CT remains broadly defined as the ability to combine algorithmic operations to form complex solutions in order to solve problems effectively, utilizing concepts of computer science with or without the use of computers. In this study, we aimed at specifying a cognitive definition of CT, focusing on the under-investigated population of primary school children. Since validated assessment tools for this age group were not available, we adapted a validated CT test, which was initially designed for middle school students. In our study participated 192 third and fourth graders. The analyses revealed promising results on the reliability of the adapted CT assessment for primary school students. Moreover, findings indicated CT's positive associations with i. complex numerical abilities, ii. verbal reasoning abilities, and iii. non-verbal visuospatial abilities. Our results indicate similarities but also differences in associations of CT with other cognitive abilities in primary school children compared to other age groups. In summary: i. numerical abilities seem to associate with CT at the primary school level, whereas this seems not the case later on in education, ii. verbal abilities seem to associate with CT both along primary and secondary education levels, and iii. non-verbal reasoning abilities seem to associate with CT from primary education level to the university level and beyond. These differences imply that several basic cognitive abilities support CT abilities and CT development differentially across ages. Highlights: The cognitive development of computational thinking is differential across age. Computational thinking builds on a convolute of several other cognitive abilities. Computational thinking is associated with verbal reasoning abilities. Computational thinking is associated with non-verbal visuospatial abilities. Computational thinking is correlated to numerical abilities in primary school.